Efficacy of Non-Linear Approach in the Study of Ozone Layer Depletion - M. Ayub Khan Yousuf Zai; M. Rashid Kamal Ansari; Afaq Ahmed Siddiqui; Faisal Ahmed Khan Afridi (Journal of Basic & Applied Sciences, 2021)
The stratosphere is one of the constituents of thermal structure of the atmosphere. The maximum concentration of ozone is found at the stratospheric region where it is interacted by many species including chemical and physical processes. Atmosphere as a whole is an open system that is regarded as a non linear system and that seems to be complex. Therefore, a non-linear trend is plausible to explain phenomenon of ozone layer depletion (OLD). In this manuscript we have paid our attention in the analysis of the major portion of historic data on stratospheric O3based on ground-based measurements by the Dobson Spectrophotometer. In this communication we have estimated parameters for describing non-linearity in the process using polynomial trend functions and predicted values are calculated for the period from 1960 to 1999. Future values for ozone depths are computed till 2006 and compared with the minor portion of the data set.